Treatment Adherence in Inflammatory Bowel Disease Patients from Argentina: A Multicenter Study - Juan Lasa; Gustavo Correa; Claudia Fuxman; Laura Garbi; Maria Eugenia Linares; Pablo Lubrano; Astrid Rausch; Martin Toro; Martin Yantorno; Ignacio Zubiaurre; Laurent Peyrin-Biroulet; Pablo Olivera (Gastroenterology Research and Practice)
Background and Aim. Treatment adherence is a frequent problem in inflammatory bowel disease (IBD). No study has assessed adherence in Argentinian patients with IBD. The aim of this study was to determine inadequate adherence to oral and parenteral therapies in patients with IBD from Argentina and to identify factors associated with it. Methods. A multicenter cross-sectional study involving seven referral centers from three cities of Argentina was undertaken. Patients with a diagnosis of ulcerative colitis (UC), Crohn’s disease (CD), or indeterminate colitis (IBDU/IC) were invited to answer an anonymous survey, which included a 5-point Likert scale to evaluate adherence to therapies. Independent variables associated with inadequate adherence were evaluated. Results. Overall, 447 UC/IBDU and 135 CD patients were enrolled. Median age was 37 years (range 21-72); 39.8% were male; median time from diagnosis was 6 years (0.5-35). 91.4% were under treatment with at least one oral medication; 50.3% of patients reported inadequate adherence to oral medications. Patients with UC/IBDU had a lower risk of inadequate adherence when compared to patients with CD (OR 0.57 (0.37-0.87)). 21.8% reported inadequate adherence to biologics; subcutaneous administration was significantly associated with inadequate adherence to biologics (OR 4.8 (1.57-14.66)). Conclusion. Inadequate treatment adherence is common among patients with IBD, and potentially modifiable factors were identified.